The Contribution of Common and Specific Therapeutic Factors to Mindfulness-Based Intervention Outcomes - Canby, Nicholas K.; Eichel, Kristina; Lindahl, Jared; Chau, Sathiarith; Cordova, James; Britton, Willoughby B. (Frontiers in Psychology, 2021)
While Mindfulness-Based Interventions (MBIs) have been shown to be effective for a range of patient populations and outcomes, a question remains as to the role of common therapeutic factors, as opposed to the specific effects of mindfulness practice, in contributing to patient improvements. This project used a mixed-method design to investigate the contribution of specific (mindfulness practice-related) and common (instructor and group related) therapeutic factors to client improvements within an MBI. Participants with mild-severe depression (N = 104; 73% female, M age = 40.28) participated in an 8-week MBI. Specific therapeutic factors (formal out-of-class meditation minutes and informal mindfulness practice frequency) and social common factors (instructor and group ratings) were entered into multilevel growth curve models to predict changes in depression, anxiety, stress, and mindfulness at six timepoints from baseline to three-month follow-up. Qualitative interviews with participants provided rich descriptions of how instructor and group related factors played a role in therapeutic trajectories. Findings indicated that instructor ratings predicted changes in depression and stress, group ratings predicted changes in stress and self-reported mindfulness, and formal meditation predicted changes in anxiety and stress, while informal mindfulness practice did not predict client improvements. Social common factors were stronger predictors of improvements in depression, stress, and self-reported mindfulness than specific mindfulness practice-related factors. Qualitative data supported the importance of relationships with instructor and group members, involving bonding, expressing feelings, and instilling hope. Our findings dispel the myth that MBI outcomes are exclusively the result of mindfulness meditation practice, and suggest that social common factors may account for much of the effects of these interventions. Further research on meditation should take into consideration the effects of social context and other common therapeutic factors.